Efficacy and safety of the addition of ertugliflozin in patients with type 2 diabetes mellitus inadequately controlled with metformin and sitagliptin: The VERTIS SITA2 placebo‐controlled randomized study. Issue 3 (23rd October 2017) - Dagogo‐Jack, Samuel; Liu, Jie; Eldor, Roy; Amorin, Guillermo; Johnson, Jeremy; Hille, Darcy; Liao, Yuqin; Huyck, Susan; Golm, Gregory; Terra, Steven G.; Mancuso, James P.; Engel, Samuel S.; et al.
Abstract : Aims: To assess ertugliflozin in patients with type 2 diabetes who are inadequately controlled by metformin and sitagliptin. Materials and Methods: In this double‐blind randomized study (Clinicaltrials.gov NCT02036515), patients (glycated haemoglobin [HbA1c] 7.0% to 10.5% [53‐91 mmol/mol] receiving metformin ≥1500 mg/d and sitagliptin 100 mg/d; estimated glomerular filtration rate [eGFR] ≥60 mL/min/1.73 m 2 ) were randomized to ertugliflozin 5 mg once‐daily, 15 mg once‐daily or placebo. The primary efficacy endpoint was change from baseline in HbA1c at Week 26; treatment was continued until Week 52. Results: A total of 464 patients were randomized (mean baseline HbA1c, 8.0% [64.3 mmol/mol]; eGFR, 87.9 mL/min/1.73 m 2 ). After 26 weeks, placebo‐adjusted least squares (LS) mean changes in HbA1c from baseline were −0.7% (−7.5 mmol/mol) and −0.8% (−8.3 mmol/mol) for ertugliflozin 5 and 15 mg, respectively (both P < .001); 17.0%, 32.1% and 39.9% of patients receiving placebo, ertugliflozin 5 mg or ertugliflozin 15 mg, respectively, had HbA1c <7.0% (53 mmol/mol). Significant reductions in fasting plasma glucose, body weight (BW) and systolic blood pressure (SBP) were observed with ertugliflozin relative to placebo. The positive effects of ertugliflozin on glycaemic control, BW and SBP were maintained through Week 52. A higher incidence of genital mycotic infections was observed in male and female patients receiving ertugliflozin (3.7%‐14.1%) vs placebo (0%‐1.9%) through Week 52. The incidence of urinary tract infections, symptomatic hypoglycaemia and hypovolaemia adverse events were not meaningfully different across groups. Conclusions: Ertugliflozin added to metformin and sitagliptin was well‐tolerated, and provided clinically meaningful, durable glycaemic control, BW and SBP reductions vs placebo over 52 weeks.